Deep structure of the Wulong goldfield, Liaodong Peninsula, China, revealed by receiver functions: implications for the tectonic and mineralization dynamics - Zheng, Fan; Xu, Tao; Ai, Yinshuang; Ge, Yunping; Zeng, Qingdong; Miao, Laicheng; Dong, Weiyu; Badal, José (Frontiers in Earth Science, 2024)
During the Mesozoic, the North China Craton experienced intense tectonic movements that resulted in the formation of numerous gold deposits on the Liaodong and Jiaodong Peninsulas in northeastern China. To investigate the relationship between deep crustal structure and gold mineralization in the Liaodong Peninsula, we deployed 334 dense seismic stations in the Wulong goldfield (WLGF) with the idea of analysing numerous receiver functions at different array stations. The purpose focused on knowing the potential for gold mineralization in the area. The study revealed the following: (1) The WLGF is characterized by a crustal thickness of approximately 32 km and an average Vp/Vs ratio of 1.76. The high value of the Vp/Vs ratio near the Wulong gold deposit suggests that mantle materials have penetrated into the crust and contributed to the mineralization process. (2) A low-velocity layer located at a depth of 10-18 km below the WLGF seems to support the existence of a potentially brittleto-ductile transition zone. Also, hydrothermal magma upwelling channels are observed in the upper crust beneath the Wulong gold deposit. (3) The presence of a discontinuous low-velocity layer in the middle crust beneath the Liaodong Peninsula suggests promising prospects for gold ore exploration. The receiver functions method based on a dense seismic array employed in this study can offer valuable references and guidance for the fine exploration and research of ore deposits in other regions globally.